Diseño e implementación de un horno automático para mejorar el proceso de ahumado de truchas. - Espín Cañar, Karina Lorena (2020)
Electromechanical engineer immersed in agro-industrial processes in the world has been focused, in solving problems in the different production systems related to product quality, in the present technological proposal is based on the design and implementation of a smoker oven for trout, whose The objective is to control the variables involved in the fish smoking process, in its case of trout, thus improving the temperature and smoke levels that will have to enter the chamber for its smoking process in the fish farm in the Province of Cotopaxi. AISI 304 stainless steel sheets were used for the construction of the Smoker Oven and in the control system a fundamental element was used such as a programmable logic controller, which allows to automate the process in an efficient way, in addition to controlling the temperature, allows reduce the consumption of LPG and the smoking time of the raw material; In addition, an operating manual for the facilitation and handling of the Oven will be developed and thus take advantage of all the advantages generated by the equipment. Finally, the furnace operability tests were carried out to verify the fulfillment of the objectives set initially to be able to perform the analysis of the variables in the smoking process and thus determine the economic and social impact that the company will obtain with its implementation